Evolutional research of the banking system on the positions of compatibility, dynamicity and self-organization - Tkachuk, Natalia (Technology audit and production reserves, 2018)
The object of research is the banking system as an economic system of micro-level, characterized by such features as: complexity, dynamism and ability to self-organization. One of the most problematic places is an understanding of the peculiarities of the steady development of the banking system from the standpoint of the synergetic approach, which allows to explain the transformational processes that were previously considered accidental, unpredictable and not subject to conceptualization. During the study, methods of abstract-logical and system analysis were used in the theoretical substantiation of the features of the modern banking system. And the method of logical generalizations in identifying features of the characteristics of a complex economic system. The study of the functioning of a modern banking system should be based on the use of the theory of systems, the theory of complex systems and the theory of dynamic systems. It is proved that the processes of self-organization can occur only in those economic systems that have a high level of complexity, are dynamic and unpredictable in the long run, which should include the banking system. It is proposed to understand the banking system as a complex, dynamic economic system: which has the mechanisms of self-organization; which can be described by integration, thermodynamic parameters, which fully reflect the exchange of material and financial resources with the environment; which is distinguished by the dynamism and unevenness of its development. This provides an opportunity to understand the laws of the functioning of the banking system, which is a prerequisite for ensuring its viability and sustainability under the influence of various exogenous and endogenous factors. Compared with the well-known system analysis, the proposed use of synergetics makes it possible to explain the progressive development of the banking system to a certain extent by fluctuations that are difficult to predict, but which are inherent to the system itself. It is in the conditions of the existence of such fluctuations that spontaneous formation of new structures in the banking system occurs, that is, self-organization takes place.